2011
DOI: 10.1074/jbc.m111.225318
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Biochemical Properties of an M1-family Aminopeptidase in Plasmodium falciparum Indicate a Role in Vacuolar Hemoglobin Catabolism

Abstract: Aminopeptidases catalyze N-terminal peptide bond hydrolysis and occupy many diverse roles across all domains of life. Here we present evidence that an M1-family aminopeptidase, PfA-M1, has been recruited to specialized roles in the human malaria parasite Plasmodium falciparum. PfA-M1 is abundant in two subcellular compartments in asexual intraerythrocytic parasites; that is, the food vacuole, where the catabolism of host hemoglobin takes place, and the nucleus. A unique N-terminal extension contributes to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
75
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(82 citation statements)
references
References 49 publications
7
75
0
Order By: Relevance
“…Details of the expression in Escherichia coli and purification of recombinant PfA-M1 (residues 192 to 1,085) will be described separately (53). Pf-LAP lacking the N-terminal Asn-rich region (residues 79-605) was expressed with a C-terminal hexahistidine tag in E. coli and purified as previously described (43).The estimated molecular mass of the purified species from size exclusion chromatography (343 kDa) was in good agreement with the predicted mass for the hexameric enzyme (357 kDa).…”
Section: Methodsmentioning
confidence: 99%
“…Details of the expression in Escherichia coli and purification of recombinant PfA-M1 (residues 192 to 1,085) will be described separately (53). Pf-LAP lacking the N-terminal Asn-rich region (residues 79-605) was expressed with a C-terminal hexahistidine tag in E. coli and purified as previously described (43).The estimated molecular mass of the purified species from size exclusion chromatography (343 kDa) was in good agreement with the predicted mass for the hexameric enzyme (357 kDa).…”
Section: Methodsmentioning
confidence: 99%
“…55 By contrast, studies by Dalal and Klemba 30 using P. falciparum parasites stably expressing yellow fluorescent protein-tagged PfM1AAP localized this enzyme to the DV and nucleus only. These cellular locations were further supported by immunoelectron microscopy 33 , and therefore Klemba and colleagues proposed that the PfM1AAP functions within the DV, releasing aminoacids from peptides generated by other endopeptidases (falcipain, plasmepsins and dipeptidase), and may have a separate role within the nucleus. In support of this theory, Ragheb et al 33 showed that while PfM1AAP exhibited less activity in the pH range 5.0 -5.5 than at a neutral pH environment (consistent with previously published data 42 ), it is still nevertheless stable and functional at acidic pH.…”
Section: Do Pfm1aap and Pfm17lap Function In The Same Or Different Cementioning
confidence: 78%
“…These cellular locations were further supported by immunoelectron microscopy 33 , and therefore Klemba and colleagues proposed that the PfM1AAP functions within the DV, releasing aminoacids from peptides generated by other endopeptidases (falcipain, plasmepsins and dipeptidase), and may have a separate role within the nucleus. In support of this theory, Ragheb et al 33 showed that while PfM1AAP exhibited less activity in the pH range 5.0 -5.5 than at a neutral pH environment (consistent with previously published data 42 ), it is still nevertheless stable and functional at acidic pH. The turnover rate (k cat ) of the enzyme did not alter dramatically at pH 5.5, and although the K m did increase with decreasing pH the authors suggested that this could be compensated for by an increased substrate concentration within the lumen of the DV.…”
Section: Do Pfm1aap and Pfm17lap Function In The Same Or Different Cementioning
confidence: 78%
See 2 more Smart Citations